MAKNA KALIMAT ISIM DALAM LAGU الحلم حان: KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE - Rohmanudin, Rohmanudin; Miftahul Mufid (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to analyze the meaning of nominal sentences (kalimat isim ) in the song الحلم حان (The Dream Has Arrived), the Arabic version of Meraih Bintang , which was part of the official campaign for the 2018 Asian Games. Using an interdisciplinary approach that combines nahwu (Arabic grammar) analysis and Charles Sanders Peirce's semiotic theory, this research uncovers both the literal and symbolic meanings of the nominal sentences in the song's lyrics. The nahwu analysis focuses on the grammatical structure of the nominal sentences, particularly the use of نكرة (indefinite) and معرفة (definite), which create impressions of universality and specificity. Meanwhile, Peirce's semiotic theory is applied to explore symbolic meanings through the triadic relationship of Representamen, Object, and Interpretant. The findings reveal that the nominal sentences in الحلم حان not only convey static descriptions or factual statements but also reflect universal values such as hope, perseverance, and success. The song also represents Arab cultural identity through the use of معرفة , while نكرة creates a universal impression relevant to international audiences. In the context of the 2018 Asian Games, the song serves as a medium to convey the spirit of sportsmanship, global unity, and collective aspirations. This study provides new insights into the application of nahwu and semiotics in modern Arabic literature and their relevance in understanding cross-cultural messages.